Unele posibilităţi de abordare interdisciplinară în studierea biologiei în şcoală [Articol] - Pîrgari, Rovim (USARB, 2021)
In the last decades, in the sciences of education, the tendency of integrating school subjects is more and more obvious. The integrated approach in preuniversity education arises from the impossibility of one of the disciplines, whatever they may be (biology, chemistry, geography, physics, etc.) to solve the complex problems of the unitary content of life, of the world in which we live. Education through school subjects is a cognitive process that seeks the development of skills and the formation of epistemological knowledge in a particular field, independent of the achievements obtained in other fields of knowledge.
Keywords: interdisciplinarity; integration; epistemological; interdisciplinary approach; histological analysis; integrated approach